Frictional characteristics of non-woven geotextile-sand interface - Gutierrez, Marte (Philippine Engineering Journal)
The use of geotextile is a recent innovation in soil stabilization. For soil reinforcement applications, adequate geotextile soil friction is necessary. A high geotextile soil friction will restrict displacement of soil around the geotextile and thus increase the strength of the soil itself. This paper presents the results of tests performed to determine the frictional behavior of the interface of sand and different types of non-woven geotextiles using a large direct shear testing machine.